In silico identification of potential inhibitors against human 2'-5'- oligoadenylate synthetase (OAS) proteins. (April 2020) - Gonzalez, Karen J.; Moncada-Giraldo, Diego M.; Gutierrez, Juan B.
Graphical abstract: Highlights: Although OAS proteins exert an antiviral role, they are also involved in the progression of several non-viral diseases. OAS acts as an immune modulator in chronic inflammatory conditions, autoimmune disorders, cancer, and infectious diseases. OAS enzymes have been ignored as drug targets, and to date, there are no compounds that can inhibit their activity. We found 37 molecules that could compete for the ATP binding sites of OAS, regardless of the activation state of the enzyme. Potential OAS inhibitors are provided, as well as valuable information for their design, development, and optimization. Abstract: As part of the type I IFN signaling, the 2′-5′- oligoadenylate synthetase (OAS) proteins have been involved in the progression of several non-viral diseases. Notably, OAS has been correlated with immune-modulatory functions that promote chronic inflammatory conditions, autoimmune disorders, cancer, and infectious diseases. In spite of this, OAS enzymes have been ignored as drug targets, and to date, there are no reports of compounds that can inhibit their activity. In this study, we have used homology modeling and virtual high-throughput screening to identify potential inhibitors of the human proteins OAS1, OAS2, and OAS3. Altogether, we have found 37 molecules that could exert a competitive inhibition in the ATP binding sites of OAS proteins, independently of the activation state of the enzyme. This latter characteristic, which might be crucial for a versatile inhibitor, was observed in compounds interacting with the residues Asp75, Asp77, Gln229, and Tyr230 in OAS1, and their equivalents in OAS2 and OAS3. Although there was little correlation between specific chemical fragments and their interactions, intermolecular contacts with OAS catalytic triad and other critical amino acids were mainly promoted by heterocycles with π electrons and hydrogen bond acceptors. In conclusion, this study provides a potential set of OAS inhibitors as well as valuable information for their design, development, and optimization.